Validation studies of outcome measures in pemphigus - Sarah Hanna; Minhee Kim, MBBS; Dedee F. Murrell, MA, BMBCh, FAAD, MD, FACD, FRCP (Edin) (Wolters Kluwer, 2016)
Pemphigus is a group of rare and potentially fatal autoimmune blistering diseases that are associated with auto-antibodies that target intercellular adhesion molecules. Incidence of pemphigus varies among populations, with the lowest incidence in Switzerland and Finland at 0.6-0.76 per million per year and the highest in Jewish communities at 16.1-32 per million per year. Pemphigus is associated with devastating morbidity and despite advancements in our understanding of the disease and a widening array of therapeutic options, no cure exists. The delay in the development of a cure may in part be attributed to the absence of a standardized and completely validated severity outcome measures to allow for high-quality multicenter control studies. Such a tool is necessary to define the best practice in clinical studies, allow for accurate comparisons between study results, justify drug use within the clinical setting, and reduce the cost burden that is associated with the use of ineffective therapies. Utilizing outcome measures that are not validated provides an opportunity to synthesize outcome measures with the intent to favor particular treatments and thus produce false conclusions. According to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) group, a validation of these measurement instruments requires investigating their responsiveness, reliability, and validity. More than 116 outcome measures exist to assess pemphigus severity, of which the Pemphigus Disease Area Index (PDAI), Autoimmune Bullous Skin Disorder Intensity Score (ABSIS), and Pemphigus Vulgaris Activity Score (PVAS) are the most comprehensively corroborated measures. With regard to validity and reliability, PDAI was unsurpassed by ABSIS and PVAS. Data indicate that ABSIS is more reliable than PVAS, but PVAS seems to have greater validity although the results are not consistent. PDAI, ABSIS, and PVAS have not yet had their responsiveness analyzed, which should be the next step to completely validate the outcome measures and conclusively determine which measure is superior. Keywords: autoimmune blistering diseases, pemphigus, outcome measures, validation, pemphigus disease area index, autoimmune bullous skin disorder intensity score